2006
DOI: 10.1074/jbc.m604601200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Residues in the C Terminus of the Bacteriophage T7 Gene 2.5 Single-stranded DNA-binding Protein

Abstract: Gene 2.5 of bacteriophage T7 encodes a single-stranded DNA (ssDNA)-binding protein (gp2.5) that is an essential component of the phage replisome. Similar to other prokaryotic ssDNAbinding proteins, gp2.5 has an acidic C terminus that is involved in protein-protein interactions at the replication fork and in modulation of the ssDNA binding properties of the molecule. We have used genetic and biochemical approaches to identify residues critical for the function of the C terminus of gp2.5. The presence of an arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 33 publications
7
78
0
Order By: Relevance
“…Similar to ssDNA, the removal of the acidic C-terminal tail results in higher affinities for these substrates. Deletion analysis of the C-terminal tail of gp2.5 demonstrated that the gradual removal of charged residues results in the gradual increase of the affinity for ssDNA (31). This observation provides further evidence that the C-terminal tail shields the ssDNA-binding cleft.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar to ssDNA, the removal of the acidic C-terminal tail results in higher affinities for these substrates. Deletion analysis of the C-terminal tail of gp2.5 demonstrated that the gradual removal of charged residues results in the gradual increase of the affinity for ssDNA (31). This observation provides further evidence that the C-terminal tail shields the ssDNA-binding cleft.…”
Section: Discussionsupporting
confidence: 52%
“…gp2.5 lacking its C-terminal phenylalanine is defective in DNA replication and is unable to grow in E. coli (31). In vitro, gp2.5 is defective in its interaction with T7 DNA polymerase in vitro.…”
mentioning
confidence: 99%
“…Interestingly, it was the acidic C= terminus of I3 that was shown to bind to the small subunit of the ribonucleotide reductase. Many SSBs have an acidic C terminus, and this region has been shown to coordinate interactions with a plethora of core components of the replication apparatus as well as auxiliary proteins involved in diverse aspects of DNA metabolism (20,31,48). I3 has very recently been shown to bind to the cellular translation initiation factor eIF4G, which relocalizes to viral factories after infection (60).…”
Section: Discussionmentioning
confidence: 99%
“…gp2.5 can stably bind to the 20-nt 5Ј-ssDNA tail, but the 5 nt ssDNA is not sufficient for binding. gp2.5 can bind to the 10-nt 5Ј-ssDNA, but the association is not stable (49). The flap endonuclease activity of gp6 on any of these substrates was not stimulated by gp2.5 over a range of concentrations (40,200, and 1000 nM) (Fig.…”
Section: Stimulation Of Gp6 Activity By T7 Gene 25 Ssdna-bindingmentioning
confidence: 99%